1999
DOI: 10.1021/jp991670y
|View full text |Cite
|
Sign up to set email alerts
|

B-Side Electron Transfer in a Rhodobacter sphaeroides Reaction Center Mutant in Which the B-Side Monomer Bacteriochlorophyll Is Replaced with Bacteriopheophytin

Abstract: The mutation, H(M182)L, in the Rhodobacter sphaeroides reaction center (RC) results in the replacement of the monomer bacteriochlorophyll on the inactive side (B-side) of the RC with a bacteriopheophytin (the new cofactor is referred to as φB). In φB containing RCs, P* stimulated emission decays with an accelerated time constant of 2.6 ± 0.1 ps at room temperature compared to 3.1 ± 0.2 ps in WT RCs. Analysis of the time-resolved spectra implies that two states are being formed during the initial reaction in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
155
1
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(184 citation statements)
references
References 27 publications
27
155
1
1
Order By: Relevance
“…Previously, it was suggested that the difference in the electronic coupling parameters in the two branches is the dominant factor. Later, experimental work cast doubt on the dominance of electronic coupling as a mechanism that causes the asymmetry in ET through branches [27,30]. Our position is that the parameters describing electron transfer from the bacteriochlorophyll dimer to bacteriochlorophyll monomers are crucial for unidirectionality.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Previously, it was suggested that the difference in the electronic coupling parameters in the two branches is the dominant factor. Later, experimental work cast doubt on the dominance of electronic coupling as a mechanism that causes the asymmetry in ET through branches [27,30]. Our position is that the parameters describing electron transfer from the bacteriochlorophyll dimer to bacteriochlorophyll monomers are crucial for unidirectionality.…”
Section: Resultsmentioning
confidence: 94%
“…The electron used only one of two possible branches. Much experimental work has been performed to solve this problem [9,10,27,28,37,38]. Generally, it is assumed that RCs have common features and the unidirectionality is caused mainly by asymmetry in the coupling integral or asymmetry in the free energy, or that both these asymmetries contribute to unidirectionality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, rapid initial charge separation to the B side has been reported in a mutant where a bacteriopheo- phytin substitutes for B B . Whereas ET from P* to this new cofactor takes place in ϳ10 ps, ET onward to H B does not occur (18), creating another, different, bottleneck in the quest for efficient use of the B side cofactors for transmembrane charge separation. Similar issues occur at the final step of ET from H B to Q B , which has a yield of only ϳ40% as mentioned above.…”
mentioning
confidence: 99%
“…Electrostatics calculations (Parson et al 1990;Alden et al 1995;Gunner et al 1996;Warshel and Parson 2001) and kinetic studies in a variety of modified reaction centers (Arlt et al 1996a, b;Heller et al 1995;Jia et al 1993;Katilius et al 1999;Kirmaier et al 1995Kirmaier et al , 2001Kirmaier et al , 2002Nagarajan et al 1993;Schmidt et al 1994) indicate that P + BChl − L is probably close to or slightly below P * in energy, while P + BChl − M lies considerably higher. Craig Schenck, Chris Kirmaier, Dewey Holten, Neal Woodbury, Arnold Hoff, Dieter Oesterhelt, Wolfgang Zinth and others have shown that mutations that lower the energy of P + BChl − M or raise the energy of P + BChl − L can increase the yield of electron transfer to the normally inactive pigments.…”
Section: Electron Acceptorsmentioning
confidence: 99%